Knowing the Arab Patrimonial Corpuses’ Introductions Between Translation, Criticism, and Creativity The Senses’ Phonetic Transcription in Soulaiman Elboustani’s Translation of Homer’s Iliad’s Introduction - Nedjela Nedjahi; Faiza Zitouni (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
The heritage corpuses’ introductions have a great importance, since their authors consider them as media for showing their trends and ideas and their sides of creativity, which are the knowledge certainties setting their method of writing with several characteristics including their objective and subjective content’s styles and the formal methodological scientific disciplines. If we come back to the Soulaiman Elboustani’s translation of Homer’s Iliad’s introduction, we find that it’s a stand-alone writing, which consists of 197 pages, in which the author addresses the criticism principles and the poetic recognising rules with deep analysis, definite accuracy, great knowledge, and addressing several topics of a great importance, after identifying the epics gender and determining whether it’s known for the Arab people or not, identifying the Homeric epic and commending it, as well as confirming its affiliation to Homer. In this research, We’ve addressed the issue of the senses’ phonetic transcription through what’s tackled by Elboustani in reviewing detailly the relationship between the line breaks, the objectives, and meanings. It was the issue addressed by numerous Arab and western researchers since antiquity.